2004
DOI: 10.1002/dvdy.20034
|View full text |Cite
|
Sign up to set email alerts
|

Identification, cloning and expression analysis of the pluripotency promoting Nanog genes in mouse and human

Abstract: The murine Nanog gene, a member of the homeobox family of DNA binding transcription factors, has been shown recently to maintain pluripotency of embryonic stem cells. We have used a sequence homology and expression screen to identify and clone the mouse and human Nanog genes and characterized their phylogenetic context and expression patterns. We report here the gene structure and expression patterns of the mouse Nanog gene, the human Nanog and Nanog2 genes, and six processed human Nanog pseudogenes. Mouse Nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
260
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(288 citation statements)
references
References 38 publications
20
260
4
Order By: Relevance
“…The different expression of CD9, nanog and taube nuss that we observed in adult myocardium could be associated to the degree of differentiation of embryonic stem cells. Indeed, it has been reported that nanog and CD9 expression was elevated in undifferentiated embryonic stem cells and down-regulated during their differentiation, in concomitance with the loss of the pluripotency (Cui et al, 2004;Hart et al, 2004). Since it has been already demonstrated that the absence of taube nuss causes apoptosis of stem cells from blastocisty inner cellular mass (Voss et al, 2000), we postulate that this factor could be important for stem cell survival even in adult heart.…”
Section: Discussionmentioning
confidence: 70%
“…The different expression of CD9, nanog and taube nuss that we observed in adult myocardium could be associated to the degree of differentiation of embryonic stem cells. Indeed, it has been reported that nanog and CD9 expression was elevated in undifferentiated embryonic stem cells and down-regulated during their differentiation, in concomitance with the loss of the pluripotency (Cui et al, 2004;Hart et al, 2004). Since it has been already demonstrated that the absence of taube nuss causes apoptosis of stem cells from blastocisty inner cellular mass (Voss et al, 2000), we postulate that this factor could be important for stem cell survival even in adult heart.…”
Section: Discussionmentioning
confidence: 70%
“…The period of loss of NANOG expression occurring at peri‐implantation (Chambers et al , 2003; Acampora et al , 2013) may enable cells of the epiblast to downregulate a number of pivotal naïve pluripotency determinants, including ESRRB (Adachi et al , 2013). In the post‐implantation epiblast, NANOG is re‐expressed (Hart et al , 2004; Osorno et al , 2012; Hoffman et al , 2013) but ESRRB is not (Adachi et al , 2013), likely due to differences in signaling environments between pre‐ and post‐implantation epiblasts. It is noteworthy that subpopulations of ESC cultures have been proposed to bear a similar character to primed pluripotent cells and vice versa (Hayashi et al , 2008; Han et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Oct4 and Nanog are essential for the maintenance of pluripotency in both hESCs and mESCs, and knockout or knockdown of either gene causes differentiation [38,39]. Oct4 and Nanog are, however, not uniquely expressed in undifferentiated hESCs: Oct4 is expressed in germ cells, and Nanog has recently been reported to be expressed in mature tissues [40,41]. Moreover, the expression of Oct4 declines slowly as cells differentiate, and the change in levels is small.…”
Section: Discussionmentioning
confidence: 99%